WAKAF PRODUKTIF (CASH WAQF) DALAM PERSPEKTIF HUKUM ISLAM DAN MAQĀṢID AL-SHARĪ‘AH - Suryani, Suryani; Isra, Yunal (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
Cash waqf is a breakthrough in appropriate with religious principles (maqāṣid al-sharī’ah) and social demands of humanity. This program can synergize with government programs in order to realize the welfare of the people of Indonesia as a manifestation of the ideals of the Republic of Indonesia, as stated in the preamble of the 1945 Constitution. Judging from the principle of religious, cash waqf has also been exemplified by several companions of Rasullullah and the scholars from time to time. Call it like what has been exemplified by the Caliph ‘Umar ibn al-Khaṭṭāb when making a land in Khaibar as productive land that used as much as possible for the benefit of Muslims. In addition, this program has also had supported by law. MUI Fatwa Commission also stipulates that the cash waqf is a movement in accordance with the principles of the religion that brought prosperity to the human in here and hereafter. This paper is literature research with reference to several primary and secondary sources such as books or books relevant to the study.***Wakaf uang merupakan gebrakan yang sesuai dengan prinsip agama (maqāṣid al-sharī’ah) dan tuntutan sosial kemanusian. Program ini bisa bersinergi dengan program-program pemerintah dalam mewujudkan kesejahteraan rakyat Indonesia sebagai manivestasi dari cita-cita besar Negara Indonesia yang tercantum dalam Pembukaan UUD 1945. Gerakan wakaf produktif dengan uang juga sudah dicontohkan oleh beberapa sahabat Rasul dan para ulama dari zaman ke zaman. Misalnya Khalifah ‘Umar ibn al-Khattāb ketika menjadikan tanah di Khaibar sebagai lahan produktif yang digunakan untuk kepentingan umat Islam. Program ini juga sudah didukung oleh hukum positif seperti Undang-Undang dan Peraturan Pemerintah tentang wakaf, Demikian pula Fatwa MUI juga menetapkan bahwa wakaf dengan menggunakan uang adalah gerakan yang sesuai dengan prinsip agama yaitu membawa kesejahteraan untuk manusia baik untuk dunia maupun akhirat mereka. Tulisan ini merupakan library research dengan merujuk beberapa sumber primer dan sekunder berupa buku atau kitab yang relevan dengan kajian.